2006
DOI: 10.1080/09537100600758719
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet Ca2+-ATPases: New markers of cell differentiation as illustrated in idiopathic scoliosis

Abstract: The aetiology of adolescent idiopathic scoliosis (AIS), the most common form of scoliosis, is unclear. Previous studies showed controversial platelet abnormalities including intracellular calcium. Platelet Ca2+ homeostasis is controlled by a multi-Ca2+-ATPase system including SERCA (sarco/endoplasmic reticulum Ca2+-ATPase) and PMCA (plasma membrane Ca2+-ATPase) isoforms. Here, we first investigated the expression of PMCA4b, SERCA3a and SERCA2b isoforms in platelets of 17 patients with AIS. Patients presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…PMA treatment resulted in an increase in GPIIIa in DAMI, CHRF 288-11 and in MEG-01 cell lines (Figures 1A and 1B and 2A and 2B), and increased Rap1b expression was observed in MEG-01 cells confirming their maturation. 24,25 PMA also induced ER stress as indicated by increase in (1) GRP-78 expression after either 1 day (CHRF 288-11 and MEG-01) or 2 days (DAMI) of treatment ( Figures 1A and 2A), (2) phosphoeIf2α in MEG-01 cells (Figure 2A and 2B), and (3) Xbp1 mRNA processing (Xbp1s) in MEG-01 cells ( Figure 2C). Similarly, TPO treatment for 2 days of DAMI cells resulted in mild maturation (increased GPIIIa expression), associated with a higher GRP-78 expression ( Figure 1C).…”
Section: Er Stress Induction During Maturation Of Megakaryocytic Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…PMA treatment resulted in an increase in GPIIIa in DAMI, CHRF 288-11 and in MEG-01 cell lines (Figures 1A and 1B and 2A and 2B), and increased Rap1b expression was observed in MEG-01 cells confirming their maturation. 24,25 PMA also induced ER stress as indicated by increase in (1) GRP-78 expression after either 1 day (CHRF 288-11 and MEG-01) or 2 days (DAMI) of treatment ( Figures 1A and 2A), (2) phosphoeIf2α in MEG-01 cells (Figure 2A and 2B), and (3) Xbp1 mRNA processing (Xbp1s) in MEG-01 cells ( Figure 2C). Similarly, TPO treatment for 2 days of DAMI cells resulted in mild maturation (increased GPIIIa expression), associated with a higher GRP-78 expression ( Figure 1C).…”
Section: Er Stress Induction During Maturation Of Megakaryocytic Cellmentioning
confidence: 99%
“…Megakaryoblastic cell-line maturation was induced using phorbol 12-myristate 13-acetate (PMA), an activator of protein kinase C, 25 or thrombopoietin (TPO). 26 Samples taken between day 1 and 3 were analyzed for ER stress and maturation markers at protein and mRNA levels.…”
Section: Er Stress Induction During Maturation Of Megakaryocytic Cellmentioning
confidence: 99%
“…Of note, there is also data that demonstrates abnormalities in the expressions of Ca 2+ ATPases (SERCA; sarco/endoplasmic reticulum Ca 2+ ATPase and PMCA; plasma membrane Ca 2+ ATPase) in platelets as well as in osteoblasts of scoliotic patients, suggesting a defect in cell differentiation involving caspase-3 (i.e., the apoptosis-like phase of the differentiation) [32]. Calmodulin regulates this system.…”
Section: Melatonin As a Factor In Ais Pathogenesis: Are The Experimenmentioning
confidence: 99%
“…Further studies on platelets performed by Bredoux et al demonstrated that the expression of Ca 2+ ATPases which regulate the megakaryocytopoiesis (platelet maturation) as well as osteoblast differentiation is abnormal in scoliosis. Further, decreased melatonin levels could account for the abnormality in platelets, because melatonin causes megakaryocyte fragmentation and modulates the cytokine network involved in platelet production [32]. As platelets are thought to resemble “miniature versions of skeletal muscle cells”, these findings suggest that abnormalities in paravertebral muscles of patients with AIS could be primary factors in development and/or progression of spinal deformities.…”
Section: Ais Modeled As a Form Of Neuromuscular Scoliosismentioning
confidence: 99%
“…The SERCA protein isoforms are translated from 3′-end alternatively spliced mRNAs which are transcribed from genes SERCA1-3 [15]. SERCA1 is expressed mainly in fast-twitch skeletal muscles, SERCA3 in several non-muscular cells including vascular endothelium, and SERCA2 in most tissues.…”
Section: Introductionmentioning
confidence: 99%